2017
DOI: 10.1073/pnas.1617482114
|View full text |Cite
|
Sign up to set email alerts
|

Essential information: Uncertainty and optimal control of Ebola outbreaks

Abstract: Early resolution of uncertainty during an epidemic outbreak can lead to rapid and efficient decision making, provided that the uncertainty affects prioritization of actions. The wide range in caseload projections for the 2014 Ebola outbreak caused great concern and debate about the utility of models. By coding and running 37 published Ebola models with five candidate interventions, we found that, despite this large variation in caseload projection, the ranking of management options was relatively consistent. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
67
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 33 publications
3
67
0
Order By: Relevance
“…What are the strength and drawbacks of this sort of analysis? Researchers quite often use the compartment models to make predictions about infectious disease outbreaks ( [27]; [19]; [18] ). This sort of model can be useful to make predictions before the outbreaks begin.…”
Section: Discussionmentioning
confidence: 99%
“…What are the strength and drawbacks of this sort of analysis? Researchers quite often use the compartment models to make predictions about infectious disease outbreaks ( [27]; [19]; [18] ). This sort of model can be useful to make predictions before the outbreaks begin.…”
Section: Discussionmentioning
confidence: 99%
“…This partially held for fast-growing epidemics with low host movement propensities as well, and has been demonstrated in detail in several wildlife-livestock spillover diseases. For instance, management models of foot-and-mouth disease (which we might categorize as a fast-growing disease with a lower movement propensity) have investigated a wide range of different management strategies and found that a variety of actions might be deemed appropriate, depending on the specific objective, the action's cost, and the prevalence at which management begins [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Within an SDM framework, managers and science experts develop the Problem statement which becomes the foundation for which management Objectives are articulated and defined. This process has been used for a number of disease management problems, including pneumonia in bighorn sheep (Sells et al, 2016), foot-and-mouth disease in livestock (Bradbury et al, 2017), chytridiomycosis in amphibians (Canessa et al, 2018), and the identification of interventions to control outbreaks of Ebola (Li, Bj, Ferrari, Mummah, & Runge, 2017), and white-nose syndrome (WNS; Szymanski, Runge, Parkin, & Armstrong, 2009) Once objectives and alternatives are agreed upon, the manager and scientists predict the Consequences of alternatives on each objective and evaluate Trade-offs among objectives.…”
Section: Introductionmentioning
confidence: 99%
“…These components comprise a "PrOACT" approach, an iterative way to facilitate insights about a decision (i.e., values focused thinking) through an SDM analysis (Hammond, Keeney, & Raiffa, 1999;Runge et al, 2013). This process has been used for a number of disease management problems, including pneumonia in bighorn sheep (Sells et al, 2016), foot-and-mouth disease in livestock (Bradbury et al, 2017), chytridiomycosis in amphibians (Canessa et al, 2018), and the identification of interventions to control outbreaks of Ebola (Li, Bj, Ferrari, Mummah, & Runge, 2017), and white-nose syndrome (WNS; Szymanski, Runge, Parkin, & Armstrong, 2009) in bats.…”
Section: Introductionmentioning
confidence: 99%